"Big Mac real" income inequality: A multinational study - Orkideh Gharehgozli; Vidya Atal (Luxembourg Income Study (LIS), 2019)
Using the Big Mac Index, we offer a simple approach to study the real income inequality. We provide a multidimensional real income inequality analysis by exploring the Coefficient of Variation and the Big Mac Affordability of households across all income deciles of 28 countries for years 2000 to 2013.
Keywords: D31; O57; 330; Big Mac Index; Income Inequality; Income Distribution Decile; Comparative Country Studies